ASSESSMENT OF TAXATION AS A FISCAL POLICY INSTRUMENT - Puzule, Anita; Žubule, Ērika (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Taxation is one of the instruments the government can actively use to have an effect on the ongoing economic processes, directing their development into the preferred route. Economic development in the world and Europe, as well as domestic issues and the accession to the community of OECD member states have created new challenges for Latvia’s development and for improvement of the national tax policy and the tax system. Latvia’s fiscal policy is not sustainable, because every year is being adjusted, thus causing dissatisfaction of society and slowing down the country's economic development in general.Aim of the research is to evalute theoretical aspects and practical application of possibilities to use the taxation as a fiscal policy instrument in order to stabilise Latvia’s national economy.Based on the experience of different countries and scientific research, the theoretical findings on the application of taxes as a fiscal policy instrument were explored, and the essential measures to be implemented in order to make Latvia’s tax system more sustainable and to reduce social inequalities, as well as to advance the economic growth were identified.The monographic method, logical constructive method, method of analysis, opinion and concept comparison method, as well as statistical data comparison were used in the research.